A review of the eriophyoid mites (Acari: Eriophyoidea) on Rubus spp. in Britain, with a new species (Diptilomiopidae) and two new records - Pye, Daniel R. L.; de Lillo, Enrico (Zootaxa, 2010)
A new vagrant species of eriophyoid mite, Asetadiptacus acarubri n. sp., is described and illustrated from Rubus fruticosus (Rosaceae) in Britain, a key to the world species of Asetadiptacus is provided, and Anthocoptes rubicolens Roivainen and Trimeroptes rubi Bagdasarian are recorded from Britain for the first time. In addition, Acalitus essigi (Hassan) and Phyllocoptes gracilis (Nalepa) are reported from R. fruticosus and Rubus sp., respectively. Collection details, distribution and host plant symptoms are provided, together with digital micrographs of the prodorsal shield and coxigenital region of a female from each species discussed. A review of the other eriophyoid mite species hitherto recorded in Britain from Rubus is also provided.